1991
DOI: 10.1021/cm00014a014
|View full text |Cite
|
Sign up to set email alerts
|

Multinuclear solid-state MAS and CP-MAS NMR study of the binding of triethyl phosphate to a montmorillonite

Abstract: The suitability of a clay for studies of the absorption/adsorption of organic molecules by multinuclear NMR spectroscopy can be judged from EPR spectra. The binding of triethyl phosphate to a montmorillonite, low in paramagnetic metal ions, has been studied by solid-state 31P and 13C NMR spectroscopy; magic angle spinning NMR spectroscopy has been used to observe mobile phases within such solids. A number of mobile and immobile phases have been detected; one important mechanism in sorption probably involves co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 0 publications
3
24
1
Order By: Relevance
“…Pratum ( 14) used 13 C NMR to study tetramethylammonium-and hexadecyltrimethylammonium-exchanged vermiculite and smectite and reported that these organocations adsorbed on clays cross-polarized very inefficiently, consistent with a high degree of mobility. O'Brien et al (15) studied triethylphosphate adsorption and intercalation on montmorillonite (5-55% w/w organic on clay) using 1 H, 13 C, and 31 P MAS and CP/MAS NMR. They were able to distinguish one liquid-like species and at least two species in a motion-restricted environment.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pratum ( 14) used 13 C NMR to study tetramethylammonium-and hexadecyltrimethylammonium-exchanged vermiculite and smectite and reported that these organocations adsorbed on clays cross-polarized very inefficiently, consistent with a high degree of mobility. O'Brien et al (15) studied triethylphosphate adsorption and intercalation on montmorillonite (5-55% w/w organic on clay) using 1 H, 13 C, and 31 P MAS and CP/MAS NMR. They were able to distinguish one liquid-like species and at least two species in a motion-restricted environment.…”
Section: Introductionmentioning
confidence: 99%
“…In a study (17) of pyridine orientation in the interlayers of kaolinite by IR, XRD, and 29 Si CP/MAS NMR, it was shown that pyridine intercalation causes a high field NMR shift of structural 29 Si in kaolinite. 15 N NMR has so far not been used to study organic compound/clay mineral interactions; however, in several studies , 15 N NMR was used to evaluate acid sites on catalysts such as zeolites (19)(20)(21)(22)(23), silica (24), silica-alumina (25,26), and alumina (27). 15 N NMR of enriched compounds is also a very common technique in biochemistry and biotechnology studies (28) because the natural abundance of 15 N is negligible (0.365%) so the 15 N NMR signal from the matrix does not contribute to the spectra.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations